The confessional diversities: advantage or disadvantage for the integration of the Western Balkans in the European Union - Karadzoski, Vladimir; Karadzoski, Mladen (Balcanica Posnaniensia. Acta et studia, 2010)
The article explores the complex relationship between religious diversity and the European integration of the Western Balkan states. The authors contextualize the issue within the broader historical and political framework of post-war Europe and the EU’s enlargement policy, emphasizing the importance of the Stabilization and Association Process as a key instrument for fostering cooperation between the EU and the region. The study aims to determine whether the region’s confessional pluralism functions as an advantage or a disadvantage in the process of EU accession. Drawing upon statistical, demographic, and sociological data, the authors examine the religious composition of seven Western Balkan countries: Croatia, Macedonia, Albania, Serbia, Montenegro, Bosnia and Herzegovina, and Kosovo. They identify how historical developments, political transformations, and social crises have shaped the interaction between religion and politics in these societies. The analysis also considers the persistence of nationalism and ecclesiastical influence as factors that both hinder and stimulate regional stabilization and democratization. The research relies on comparative and analytical methods, using official demographic data, EU documents, and scholarly sources to assess the extent to which religious coexistence contributes to or obstructs the Europeanization of the Balkans. The authors conclude that confessional diversity in itself is neither a barrier nor a facilitator of EU integration; rather, the quality of interreligious relations determines its impact. Constructive interfaith dialogue, mutual tolerance, and cooperation among religious communities can serve as a catalyst for integration, while interconfessional conflicts remain a serious obstacle. Ultimately, the article highlights that the European future of the Western Balkans depends as much on social reconciliation and cultural transformation as on the fulfillment of formal political and economic criteria.